TINGKAT UPAH KAITANNYA TERHADAP KESEJAHTERAAN PEKERJA DI DAERAH KUREKSARI WARU SIDOARJO - M. Yasin Yusuf, (Pendidikan Ekonomi, 2010)
The informal sector has an important role in contributing to development, because the informal sector absorbs labor (especially lower-class society) significantly reducing the urban unemployment problem and increase the income of urban poor. In addition, the informal sector to contribute to government revenue of the city. Informal sector growth is not rapid enough balanced with the welfare of its workers.. As in the Kureksari Waru, in the area there are many cottage industries engaged in the world where industrial blacksmiths were included in the informal sector.